SORM-Based Probabilistic Analysis of Pile in 2-Layer under Lateral Spread Soil - Farag, Reda; Haldar, Achintya; El-Meligy, Mahmoud (New Approaches in Engineering Research Vol. 10, 2021)
The lateral ground spreading has witnessed an increase in interest due to its serious effect and major destructive character during and after seismic events. This paper describes a quick method for predicting pile failure due to lateral spread. The proposed technique integrates the limit equilibrium method (LEM) with the second order reliability method (SORM). In this technique, a limit equilibrium-based finite element model is coupled with (SORM) via the response surface method (RSM). In the finite element model the soil is represented by 3D solid elastoplastic (Drucker-Prager failure criterion) while the pile is represented by elastic 3D beam element. Monte Carlo Simulation (MCS) is used to validate the suggested method through numerical example. Both operational and structural limit states are involved. For the considered example, the soil pressure and the pile radius are found to be the most sensitive variables.